An Analysis of Students' Writing Anxiety in English Learning at Grade XII MIPA 3 of SMAN 6 Padang - Rulyandi, Ilham (e-Journal of Linguistics, 2022)
This study aims to analysis of students’ writing anxiety   in English learning at SMAN 6 Padang grade XII MIPA 3. This research is qualitative. The techniques of collecting data are Questionnaire and interview. The subject of this research was 36 students’ of XII MIPA 3. The purpose of this research is analyzed what factors cause students to be anxious about writing in English learning in grade XII MIPA 3 SMAN 6 Padang. The results of the data that have been obtained with the cognitive problems is the factors that most influence students’ anxiety in writing English especially in grade XII MIPA 3 at SMAN6 Padang, and from internal factors influencing students’ anxiety in writing English factor problem of word choice has the lowest score from internal factors in writing English classroom, it scores was 31.86%. And from external factors lowest score is lack of knowledge about writing stages, it score was 32.03%